FORMULATION OF BROWNIES COOKIES WITH THE ADDITION OF TEMPE FLOUR AND COFFEE GROUNDS AS FOOD PROCESSING - Miguel Nathaniel Tirukan; Bambang Sigit Sucahyo; Kejora Handarini; Rachma Nur Devianti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Brownie cookies are generally made using wheat flour as the main ingredient. Substituting wheat flour with tempeh flour has the potential to increase the nutritional value of the product because tempeh flour has a higher content of protein, essential amino acids, and dietary fiber. Coffee grounds are coffee processing waste that still contain bioactive compounds and fiber so they have the potential to be used as an additive that can affect aroma and sensory characteristics. This study aims to determine the effect of tempeh flour substitution and the addition of coffee grounds on the protein, fiber, carbohydrate content, and organoleptic quality of brownie cookies. The study used an experimental method with a factorial Completely Randomized Design (CRD), consisting of two factors: tempeh flour substitution (30%, 70%, 30%, 70%) and the addition of coffee grounds (6%, 6%, 9%, 9%). The parameters tested included protein content, fiber content, carbohydrate content, and organoleptic tests (color, aroma, taste, and texture). Proximate data were analyzed using ANOVA, while organoleptic data were analyzed using the Kruskal-Wallis test.